ANALISIS MENU Aâ€™LA CARTE DALAM MENENTUKAN BAURAN PEMASARAN PADA EDEN RESTAURANT DI DHYANA PURA BEACH HOTEL SEMINYAK KUTA BALI - Agus Muriawan Putra; I Komang Tri Suta Guna (Jurnal Ilmiah Hospitality Management, 2011)
Menu that offered to a customer need to be analysis periodically, it is expected company be able to obtain optimal revenues can be used for business development in the future. Dhyana Pura Beach Hotel before used only with history of sales to make menu, will not had result of analysis well. How to solve that problem, they used analysis menu engineering to get profit, popular and class of menu. Based on the problem background, then aim of this research are: 1) to know analysis aâ€™la carte menu at Eden Restaurant Dhyana Pura Beach Hotel, Seminyak, Kuta-Bali period July-December 2009 s/d January-June 2010; 2) to know marketing mix strategy to aâ€™la carte menu at Eden Restaurant Dhyana Pura Beach Hotel, Seminyak, Kuta-Bali.Aim of this report was formulated of marketing strategy with several of marketing programs. Dataâ€™s was collected by observation, interview, and bibliography study, and later use 4P (marketing mix) there are: â€œproductâ€ they are starters, soup, salad, entrees, mains, Balinese & Indonesian, snack and dessert; â€œpriceâ€ which each menu have each price; â€œplaceâ€ is by method using direct distribution; â€œpromotionâ€ composed of advertising, personal selling, promotion sale, and publicity. Afterwards with used menu engineering analyzis is a term to describe a mathematical model about menu contribution margin and menu popularity calculation in order to determinate menu classes or categories. Pursuant to research result, it can be known from menu offered by Dhyana Pura Beach Hotel has 21 menu or 38,2% classified star, means popular and profiting, 12 menu or 21,82% classified plowhorse, means popular not too profit, 15 menu or 27,27% classified puzzle, means less popular but profiting, and 7 menu or 12,73% classified dog, means less popular and less profit. Based on result of solution earns in giving suggestions that is doing analysis menu periodically by using analysis menu engineering at Dhyana Pura Beach Hotel, then give attention to menu category like star, plowhorse, puzzle and dog, so it will give profit that company needed.